Management of refractory septic shock. Can intra-aortic balloon counterpulsation be the answer? - Shrestha, Gentle Sunder; Nepal, Gaurav (Nepal Mediciti Medical Journal, 2021)
Refractory septic shock (RSS) is a subset of septic shock that does not respond to standard resuscitation and to high-dose vasopressor therapy. Management of RSS remains challenging and is associated with increased mortality. There is a dire need to identify a novel therapeutic strategy for the management of RSS. Extracorporeal membrane oxygenation (ECMO) and intra-aortic balloon counterpulsation (IABP) are potential options for the management of RSS. Since ECMO is expensive, requires high expertise, and has more complications, IABP can be a feasible therapeutic option. IABP may help clinicians buy the time by supporting the organ perfusion while treating sepsis. Judicious patient selection can be the key. Well designed clinical trials may be the way forward.